Early salvage total mesorectal excision (sTME) after organ preservation failure in rectal cancer does not worsen postoperative outcomes compared to primary TME: systematic review and meta-analysis - Chaouch, Mohamed Ali; Khan, Jim; Gill, Talvinder Singh; Mehrabi, Arianeb; Reißfelder, Christoph; Rahbari, Nuh Nabi; Elhadedy, Hazem; Oweira, Hani (International journal of colorectal disease, 2021)
While oncological outcomes of early salvage total mesorectal excision (sTME) after local excision (LE) have been well studied, the impact of LE before TME on postoperative outcomes remains unclear. We aimed to compare early sTME with a primary TME for rectal cancer.
Published online: 9 July 2021
Gesehen am 14.08.2023